Correlation study of male semen parameters and embryo aneuploidy in preimplantation genetic testing for aneuploidy - Yang, Hongyi; Liu, Yan; Niu, Wenbin; Yang, Zilan; Wang, Yang; Jin, Haixia; Li, Gang (Frontiers in Endocrinology, 2023)
Objective The purpose of this study was to evaluate the influence of abnormal semen parameters on embryo aneuploidy based on single nucleotide polymorphism microarray (SNP array). Methods A total of 464 blastocysts from 103 PGT-A cycles were analyzed. The embryo quality and embryo aneuploidy rates were compared between different groups which divided by male semen parameters (sperm concentration, motility, morphology, and DFI) according the WHO criteria (2021). Results The total blastocysts chromosome aneuploidy rate was 42.3% (191/452). In the teratozoospermia group, the good-quality embryo and blastocyst formation rate were lower than the normal group(44.4% vs 60.7%, P <0.01; 33.3% vs 43.5%, P <0.05), The good-quality embryo rate in normal DFI group was significantly higher than high-DFI group (59.0% vs 48.4%, P < 0.05). The blastocyst aneuploidy rate in low sperm concentration group, and high DFI group was no differences between with that in normal sperm concentration and DFI group (47.7% vs 37.8% and 44.7% vs 37.8%, P>0.05). The aneuploid rate of blastocyst in teratozoospermic and asthenozoospermia group was significantly higher than that of normal morphology and motility group (50.0% vs 34.0% and 46.7% vs 33.7%, P<0.05). Conclusion Our study revealed that sperm DFI were positively correlated with blastocyst aneuploidy rate, while sperm motility and sperm morphology rate were negatively correlated with blastocyst aneuploidy rate. Abnormal semen parameters may affect embryo quality and increase the aneuploidy rate of blastocyst chromosomes, suggesting that in clinical practice of assisted reproduction patients with abnormal semen parameters can be treated in advance to improve sperm quality, so as to reduce the impact on embryo quality and achieve a better pregnancy outcome.